"Oris Duplicatio"—Duplication of the Oral Cavity a Rare Malformation in a 10-Month-Old Child: State of the Science and Management. Issue 8 (5th November 2022) - Delay, Alexandra; Morand, Beatrice; Hacini, Lyna; Lewandowski, Mehdi; Baudin, Florent; Bachelet, Jean-Thomas
Abstract : The authors report the case of a 10-month-old child with total oral duplication. The authors review this pathology and the diagnostic and treatment modality through the few cases described in scientific history. The discussed etiopathogeny of this rare malformation is detailed in this work.